Dietary intakes of women with Type 1 diabetes before and during pregnancy: a pre‐specified secondary subgroup analysis among CONCEPTT participants. - Neoh, S. L.; Grisoni, J. A.; Feig, D. S.; Murphy, H. R. (Diabetic Medicine, 2020)
Aim: To describe the dietary intakes of women with Type 1 diabetes before and during pregnancy. Methods: This was a pre‐specified subgroup analysis of CONCEPTT involving 63 women planning pregnancy and 93 pregnant women from 14 sites in England, Scotland and Ireland. Two hundred and forty‐six 3‐day food diaries (104 planning pregnancy, 142 pregnant) were matched to data source and food reference codes, and analysed using dietary software. Participants were informed that food diaries would be de‐identified and used only for research purposes. Results: Mean (sd) daily energy intake was 1588 (346) kcal and 1673 (384) kcal in women planning pregnancy and pregnant women respectively. Total carbohydrate intake was consistent with dietary guideline recommendations [180 (52) g planning pregnancy, 198 (54) g pregnant], but non‐recommended sources (e.g. sugars, preserves, confectionery, biscuits, cakes) contributed to 46% of total daily carbohydrate intake. Fat consumption exceeded guideline recommendations [70 (21) g planning pregnancy, 72 (21) g pregnant]. Fibre [15.5 (5.3) g planning pregnancy, 15.4 (5.1) g pregnant], fruit and vegetable intakes [3.5 (2.2) and 3.1 (1.8) serves/day] were inadequate. Twelve women planning pregnancy (19%) and 24 pregnant women (26%) did not meet micronutrient requirements. Conclusions: The diets of pregnant women from England, Scotland and Ireland are characterized by high fat, low fibre and poor‐quality carbohydrate intakes. Fruit and vegetable consumption is inadequate, with one in four women at risk of micronutrient deficiencies. Further research is needed to optimize maternal nutrition for glycaemic control and for maternal and offspring health. What's new?: Maternal glycaemic control is the main modifiable determinant of pregnancy outcomes in Type 1 diabetes. Maternal diet influences insulin dosing and glycaemia; and contributes to the overall health of the mother, yet this has not been described previously.This study demonstrates that pregnant women with Type 1 diabetes have higher than recommended intakes of fat and inadequate intakes of fibre, fruit and vegetables.One in four women are at risk of micronutrient deficiencies suggesting substantial scope for improvement.Further research is required to understand how to optimize maternal nutrition both for achieving glucose control targets and for improving overall maternal and infant health.